Experimental study of heat storage unit made of PCM-gypsum composite integrated with the ventilation system of the building - Jaworski, Maciej; Jędrzejuk, Hanna; Laskowski, Rafał (International Conference “Environmental Engineering”, 2017)
In the paper a special heat storage unit for building applications is presented. It has a form of a ceiling panel that is made of PCM-gypsum mortar composite and it contains internal channels for air flow, since it is designed as a part of ventilation system of the building. The panel works as a regenerative heat exchanger with phase change material (PCM) as a prevailing heat storage medium. When a melting point of PCM is properly chosen it is possible that air temperature flowing into the building reach a level corresponding to thermal comfort conditions, regardless the temperature at the intake. Warm air (during a day) releases heat basically to PCM causing its melting. During night time cool ambient air is heated up while it takes back heat accumulated in PCM. An experimental set-up based on the above concept was developed. A series of tests in different conditions (for variable inlet air temperatures, air flow rates) were performed. Information on thermal performance of the ceiling panel as well as detailed data on heat transfer process were obtained and discussed in the paper.
Keywords: thermal energy storage; night ventilation; building materials; phase change materials